An appraisal of Access to Learning in the early years: Employing Innovation and Technology - Etobro, Akpezi Benjamin; Odebowale, Ireti Tina; Isioma, Isioma; Olagunju, Olagunju (Universitas Negeri Malang, 2022)
Access to education in terms of quality has become a major source of concern for educators, parents, caregivers, special interest groups and related agencies. Given that the early years are a crucial period in the life of the child, it is expedient to come up with measures that will guarantee access to education for all.It is against this background that this paper examined the measures that can facilitate and enable learning employing innovative practices through technology. The research design used for the study is survey research design of the descriptive type. A simple random sampling technique was used to select teachers who are the participants of the study. A total of 100 teachers were sampled. One research instrument was used to collect data from the respondents. There was a significant difference between male and female teachers in their perception about accessibility to education through innovation and technology (t = 2.46; df =86; P< 0.05). However, there was no significant difference in the perception of Early Childhood Education teachers on the integration of technology based on their educational qualification (F(3,84) =1.380; P>0.05).It was concluded that teachers should be provided with an enabling technologically assisted environment to enhance their technological pedagogy.